Deer presence rather than abundance determines the population density of the sheep tick, Ixodes ricinus, in Dutch forests - Hofmeester, Tim R.; Sprong, Hein; Jansen, Patrick A.; Prins, Herbert H. T.; van Wieren, Sipke E. (Parasites & vectors, 2017)
Background Understanding which factors drive population densities of disease vectors is an important step in assessing disease risk. We tested the hypothesis that the density of ticks from the Ixodes ricinus complex, which are important vectors for tick-borne diseases, is determined by the density of deer, as adults of these ticks mainly feed on deer. Methods We performed a cross-sectional study to investigate I. ricinus density across 20 forest plots in the Netherlands that ranged widely in deer availability to ticks, and performed a deer-exclosure experiment in four pairs of 1 ha forest plots in a separate site. Results Ixodes ricinus from all stages were more abundant in plots with deer ( n = 17) than in plots without deer ( n = 3). Where deer were present, the density of ticks did not increase with the abundance of deer. Experimental exclosure of deer reduced nymph density by 66% and adult density by 32% within a timeframe of two years. Conclusions In this study, deer presence rather than abundance explained the density of I. ricinus . This is in contrast to previous studies and might be related to the relatively high host-species richness in Dutch forests. This means that reduction of the risk of acquiring a tick bite would require the complete elimination of deer in species rich forests. The fact that small exclosures (< 1 ha) substantially reduced I. ricinus densities suggests that fencing can be used to reduce tick-borne disease risk in areas with high recreational pressure.